Zmienność litologiczna gruntów w wybranym profilu badawczym zlokalizowanych w obrębie zbiorników pokopalnianych w rejonie Łęknicy = The litological variability of ground in the chosen investigation?s profiles whithim of anthropogenic lake in Łęknica region - Hudak, Magda (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In article described litological variability of ground in the chosen investigation?s profiles whithim of anthropogenic lake in Łęknica region. This prroblem determined os introduction in further investigations which will been realized in this region in the space of EFRR INTERREG IIIA. Poland Programme-Germany. Purpose of programme is valuation possibility improved quality water resources in after coal mine lakes and subsoil water in Sprewa-Nysa-Bóbr Euroregion.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); pojezierze antropogeniczne; rodzaj gruntów; zawartość substancji organicznej; anthropogenic lake; types of grounds; contents of organic substance